The burden of abdominal obesity with physical inactivity on health expenditure in Brazil - Codogno, Jamile S. [UNESP]; Turi, Bruna C. [UNESP]; Sarti, Flávia M.; Fernandes, Rômulo A. [UNESP]; Monteiro, Henrique L. [UNESP] (FapUNIFESP (SciELO), 2015)
The purpose of this study was to analyze the association between the clustering of physical inactivity with abdominal obesity and public health care expenditure in Brazilian adults. The sample was composed of 963 patients of both genders, randomly selected in the Brazilian Public Health care System during 2010. Entire health care expenditures during the last year were computed and stratified into: medical consultations, medication dispensing, laboratory tests and overall expenditure. Waist circumference was used to diagnose abdominal obesity and physical activity was assessed by previously validated questionnaire. Sedentary and abdominally obese patients (OR= 3.01 [OR95%CI= 1.81-4.99]) had higher likelihood be inserted in the group of higher expenditures than only abdominally obese patients (OR= 1.66 [OR95%CI= 1.07-2.59]). There is a synergic effect between abdominal obesity and physical inactivity on overall health care expenditures.
Keywords: Epidemiology; Expenditures; Obesity; Physical activity